Spatial Adaptation of Traditional Javanese Houses in Landscape Design of Senaputra Cultural Tourism Park - Suwarlan, Stivani Ayuning (Local Wisdom Jurnal Ilmiah Kajian Kearifan Lokal, 2021)
One of the efforts to preserve Indonesian culture and heritage is through cultural tourism parks. Therefore, the existence of a cultural tourism park is very important because it has Indonesian cultural values. The problem currently faced by Indonesia, especially Malang City, East Java, is the number of new modern tourism parks that make cultural tourism parks less attractive. The rise number of modern tourism parks in Malang has reached 100% in the last 5 years, while there has been no addition of cultural parks in Malang. As what happened at the Senaputra Cultural Tourism Park, Malang that is famous as a park that preserves traditional culture, especially East Java culture. In the glorious era of Taman Senaputra in 1980s, traditional East Javanese dances and wayangkulit performances were often held. The research method used quantitative and qualitative research. First, through observation to determine the factual conditions of the research area using walkthrough analysis techniques. Second, through questionnaires to find out communities perceptions of preferences between modern parks compared to cultural parks and to find out the communities perception of the Senaputra cultural park main problems. The results of the questionnaire were processed using SPSS and analyzed using a linkert scale to determine the priority scale of main problems. The results of this study showing people preferences and perception index score of modern park 82.04% and cultural park 17.96%. The main problem of less preferences index score of cultural park is due to of the irregular landscape arrangement of the cultural park and does not have the characteristics of Javanese culture as a cultural park and author observation’s resulted that this park also lacks of maintenance and most of park elements are damaged, so there is a need for design directions from the landscape side which has the character of Javanese culture in an effort to revive (revitalize) the cultural tourism park so that it is again in demand and cultural values as the national identity are not forgotten and lost DOI: https://doi.org/10.26905/lw.v13i1.4770